13.4k views
7 votes
What's 4x + 3y = 6 4x - y = 2​

User Tyana
by
5.9k points

2 Answers

12 votes

Answer:

(
(3)/(4), 1 )

Explanation:

Given the 2 equations

4x + 3y = 6 → (1)

4x - y = 2 → (2)

Subtract (2) from (1) term by term to eliminate x

4x - 4x + 3y - (- y) = 6 - 2, that is

4y = 4 ( divide both sides by 4 )

y = 1

Substitute y = 1 into either of the 2 equations and solve for x

Substituting into (1)

4x + 3(1) = 6

4x + 3 = 6 ( subtract 3 from both sides )

4x = 3 ( divide both sides by 4 )

x =
(3)/(4)

solution is (
(3)/(4), 1 )

User Asdine
by
5.8k points
6 votes

Answer:

Explanation:

4x + 3y = 6 -----------------(I)

4x - y =2 ---------------------(II)

Multiply (II) by (-1) and then add

(I) 4x + 3y = 6

II) *(-1) - 4x + y = - 2 {Now add, x will be eliminated}

4y = 4

y= 4/4

y= 1

Plugin y =1 in equation (I)

4x +3*1 = 6

4x + 3 = 6

4x = 6- 3

4x = 3

x = 3/4

User Sayou
by
5.5k points